Adenosine A1 receptor activation attenuates cardiac hypertrophy and fibrosis in response to α1‐adrenoceptor stimulation in vivo. (16th November 2015) - Puhl, S‐L; Kazakov, A; Müller, A; Fries, P; Wagner, D R; Böhm, M; Maack, C; Devaux, Y
Abstract : Background and Purpose: Adenosine has been proposed to exert anti‐hypertrophic effects. However, the precise regulation and the role of the different adenosine receptor subtypes in the heart and their effects on hypertrophic signalling are largely unknown. We aimed to characterize expression and function of adenosine A1 receptors following hypertrophic stimulation in vitro and in vivo . Experimental Approach: Pro‐hypertrophic stimuli and adenosine A1 receptor stimulation of neonatal rat cardiomyocytes and male C57/Bl6 mice, sc. drug administration, real‐time PCR, 3 [H]‐leucine‐incorporation assay, immunostaining, tissue staining, Western blots, gravimetric analyses and echocardiography were applied in this study. Key Results: In neonatal rat cardiomyocyte cultures, phenylephrine, but not angiotensin II or insulin‐like growth factor 1 (IGF1), up‐regulated adenosine A1 receptors concentration‐dependently. The hypertrophic phenotype (cardiomyocyte size, sarcomeric organization, total protein synthesis, c‐fos expression) mediated by phenylephrine (10 μM), but not that by angiotensinII (1 μM) or IGF1 (20 ng·mL −1 ), was counteracted by the selective A1 receptor agonist, N6‐cyclopentyladenosine. In C57/BL6 mice, continuous N6‐cyclopentyladenosine infusion (2 mg·kg −1 ·day −1 ; 21 days) blunted phenylephrine (120 mg·kg −1 ·day −1 ; 21 days) induced hypertrophy (heart weight, cardiomyocyte size and fetal genes), fibrosis, MMP 2 up‐regulation and generation of oxidative stress – all hallmarks of maladaptive remodelling. Concurrently, phenylephrine administration increased expression of adenosine A1 receptors. Conclusions and Implications: We have presented evidence for a negative feedback mechanism attenuating pathological myocardial hypertrophy following α 1 ‐adrenoceptor stimulation. Our results suggest adenosine A1 receptors as potential targets for therapeutic strategies to prevent transition from compensated myocardial hypertrophy to decompensated heart failure due to chronic cardiac pressure overload.